Effet de l'élaboration d'hypothèses sur la compréhension de l'oral et sur les stratégies d'autorégulation de l'écoute en langue seconde : une étude empirique. - Stéphanie Roussel; André Tricot (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
The present study aims to clarify the effect of the type of anticipation on oral comprehension and on listening strategies. After a pretest, 24 second-year law students learning German were divided into three same-level groups. The first group had to listen to an oral document in German without any pre-listening activity. Before the listening task, the second group proposed hypotheses about the lexicon. The third group formulated hypotheses on the content of that document. Each participant listened to the document on a computer. Each screen was filmed so that pauses and rewinds could be recorded. After the listening stage, all the participants wrote down what they had understood of the document in French. We then compared the performances in comprehension of the three groups, analyzed the French written recall of the students and the self-regulation listening strategies (pauses and rewinds) they opted for. Our results show that, even though the initial level greatly affects oral comprehension, the type of anticipation formulated before the listening task can, in certain cases, influence the way the listener recalls the oral text and regulates his listening task.